6
$\begingroup$

Evaluate $$\int_{0}^{\pi/2}\dfrac{\sin^6 x}{\sin x + \cos x}\text{ d}x$$

Is there a nice, elegant way of solving the above integral?

Here's what I did - Replaced $f(x)$ by $f(\pi/2-x)$, added and got rid of some common factors in numerator and denominator. This was followed by indefinite integration, and ultimately substituting the limits in the final expression.

The above method is kind of long, though - and I'm wondering if there's a quicker, shorter and rather elegant way of getting around this integral. Could someone post a solution, and share ideas?

Thanks a lot.

$\endgroup$
  • 1
    $\begingroup$ Please use MathJax to format your equations so that they are searchable, rather than images. $\endgroup$ – Clarinetist Jul 2 '18 at 13:30
  • $\begingroup$ If your integral is denoted by $I$, then $$2I=\int_0^{\pi/2} \frac{\sin^6 x + \cos^6 x}{\sin x + \cos x} \mathrm{d}x$$ $\endgroup$ – Crostul Jul 2 '18 at 13:43
  • $\begingroup$ Did that, what's next? $\endgroup$ – arya_stark Jul 2 '18 at 13:44
  • $\begingroup$ Is it true that $$ 8I=\int_0^{2\pi} \frac{\sin^6 x + \cos^6 x}{\sin x + \cos x} \mathrm{d}x$$ ?. I think it won't be a bad idea to use integration in the complex circle (see math.stackexchange.com/questions/308693/…) then, if it's possible. $\endgroup$ – Gonzalo Benavides Jul 2 '18 at 17:01
3
$\begingroup$

I have solved it first as a indefinite integral and then as a definite integral. I am not sure how different it is with yours. Good luck. Let me know if you have any questions.

enter image description here

$\endgroup$
3
$\begingroup$

A standard way for dealing with trigonometric integrals is to exploit the substitution $x=2\arctan\frac{t}{2}$.
Here it leads to $$ \int_{0}^{\pi/2}\frac{\sin^6 x}{\sin x+\cos x}\,dx = 128\int_{0}^{1}\frac{t^6}{(2t+1-t^2)(t^2+1)^6}\,dt$$ and the last integral can be computed by partial fraction decomposition. It equals $$ \frac{1}{8}\left(2+\sqrt{2}\,\text{arctanh}\frac{1}{\sqrt{2}}\right)\approx\frac{28}{69}. $$ This also follows from $\sin x+\cos x=\sqrt{2}\cos\left(x-\frac{\pi}{4}\right)$ and $$ \int_{-\pi/4}^{\pi/4}\frac{\sin^6\left(x+\frac{\pi}{4}\right)}{\sqrt{2}\cos x}\,dx=\frac{1}{8\sqrt{2}}\sum_{k=0}^{6}\binom{6}{k}\int_{-\pi/4}^{\pi/4}\sin^k(x)\cos^{5-k}(x)\,dx $$ where the contribution provided by odd $k$s is zero and $$ 2\int_{0}^{\pi/4}\cos(x)^5\,dx =\frac{43}{30\sqrt{2}},\qquad 2\int_{0}^{\pi/4}\sin(x)^2\cos(x)^3\,dx =\frac{7}{30\sqrt{2}}$$ $$ 2\int_{0}^{\pi/4}\sin(x)^4\cos(x)^1\,dx =\frac{3}{30\sqrt{2}}$$ $$2\int_{0}^{\pi/4}\sin(x)^6\cos(x)^{-1}\,dx =-\frac{73}{30\sqrt{2}}+4\,\text{arctanh}\tan\frac{\pi}{8}.$$

$\endgroup$
3
$\begingroup$

Hint:

$$2I=\int_0^{\pi/2}\dfrac{\sin^6x+\cos^6x}{\sin x+\cos x}dx$$

Now $\sin^6x+\cos^6x=(\sin^2x+\cos^2x)^3-3\sin^2x\cos^2x(\sin^2x+\cos^2x)=1-3\sin^2x\cos^2x$

and $\sin^2x\cos^2x=\dfrac{\sin^22x}4=\dfrac{1-\cos4x}8$

For $J=\displaystyle\int_0^{\pi/2}\dfrac{\cos4x}{\sin x+\cos x}dx=\int_0^{\pi/2}\dfrac{\cos4x}{\sqrt2\cos\left(x-\dfrac\pi4\right)}dx,$

set $x-\dfrac\pi4=y,\cos4x=\cos4\left(y+\dfrac\pi4\right)=\cos(4y+\pi)=-\cos4y$

$\implies-\sqrt2J=\displaystyle\int_{-\pi/4}^{\pi/4}\dfrac{\cos4ydy}{\cos y}=\int_{-\pi/4}^{\pi/4}\dfrac{1-8\cos^2y+8\cos^4y}{\cos y}dy$

Now use $\cos3y=4\cos^3y-3\cos y $

$\endgroup$
1
$\begingroup$

Let $J$ be the integral to be calculated, we want to get the computer result, here using sage:

sage: var('x');
sage: J = integral( sin(x)^6/(sin(x)+cos(x)), x, 0, pi/2 )
sage: J
1/16*sqrt(2)*log((2*sqrt(2)) + 3) + 1/4

For this, we use the simple idea of getting a $\sin(x+\pi/4)$ (up to a multiplicative constant) in the denominator, then do trivial computations...: $$ \begin{aligned} J &=\int _0^{\pi/2} \frac{\sin^6 x}{\sin x + \cos x}\;dx \\ &=\int _0^{\pi/2}\frac 1{\sqrt 2} \frac{\sin^6 x}{\frac 1{\sqrt 2}\left(\sin x + \cos x\right)}\;dx \\ &=\frac 1{\sqrt 2} \int _0^{\pi/2} \frac {\sin^6 x} {\sin \left(x + \frac\pi4\right)}\;dx \\ &\qquad\text{Substitution: }y = x+\frac \pi 4\ , \\ &=\frac 1{\sqrt 2} \int_{\pi/4}^{3\pi/4} \frac {\sin^6 \left(y- \frac\pi4\right)} {\sin y}\;dy \\ &=\frac 1{\sqrt 2} \int_{\pi/4}^{3\pi/4} \frac 18\cdot\frac 1{\sin y} \Big(\ \sin y-\cos y\ \Big)^6\;dy \\ &=\frac 1{\sqrt 2} \int_{\pi/4}^{3\pi/4} \frac 18\cdot\frac 1{\sin y} \Big(\ \sin^6 y -6\sin^5y\cos y +15\sin^4y\cos^2 y \\&\qquad\qquad -20\sin^3y\cos^3 y +15\sin^2y\cos^4 y -6\sin y\cos^5 y +\cos^6 y \ \Big)\;dy \\ &=\frac 1{8\sqrt 2} \int_{\pi/4}^{3\pi/4} \Big(\ \sin^5 y -6\sin^4y\cos y +15\sin^3y\cos^2 y \\&\qquad\qquad -20\sin^2y\cos^3 y +15\sin y\cos^4 y -6\cos^5 y +\frac{\cos^6 y}{\sin y} \ \Big)\;dy \\ &= \frac 1{8\sqrt 2} \int_{\pi/4}^{3\pi/4}\left[\ \begin{aligned} -(1-\cos^2y)^2 &\,\cdot\,\cos 'y \\ - 6\sin^4y &\,\cdot\,\sin'y \\ - 15(1-\cos^2y)\cos^2y &\,\cdot\,\cos'y \\ - 20\sin^2y(1-\sin^2 y) &\,\cdot\,\sin'y \\ - 15\cos^4y &\,\cdot\,\cos'y \\ - 6(1-\sin^2 y)^2 &\,\cdot\,\sin'y \\ -\frac{\cos ^6y}{1-\cos^2 y}&\,\cdot\,\cos'y \end{aligned} \ \right]\; dy \\ &= \frac 1{8\sqrt 2} \int_{\pi/4}^{3\pi/4}\left[\ \begin{aligned} -(1-\cos^2y)^2 & \\ - 15(1-\cos^2y)\cos^2y & \\ - 15\cos^4y & \\ -\frac{\cos ^6y}{1-\cos^2 y}& \end{aligned} \ \right]\,\cdot\,\cos 'y\; dy \\ &\qquad\text{because for the $\sin'y$-terms we have $\sin(\pi/4)=\sin(3\pi/4)$...} \\ &\qquad\text{Substitution: }u=\cos t\ ,\ du=\cos't\, dt\ , \\ &= \frac 1{8\sqrt 2} \int_{-1/\sqrt2}^{1/\sqrt2}\left[\ (1-u^2)^2 +15(1-u^2)u^2 +15u^4 +\frac {u^6-1+1}{1-u^2} \right] \; du \\ &= \frac 1{4\sqrt 2} \int_0^{1/\sqrt2}\left[\ (1-u^2)^2 +15(1-u^2)u^2 +15u^4 -(1+u^2+u^4) +\frac {1}{1-u^2} \right] \; du \\ &= \frac 1{4\sqrt 2} \int_0^{1/\sqrt2}\left[\ 12u^2 +\frac {1}{1-u^2} \right] \; du \\ &= \frac 1{4\sqrt 2} \left[\ 4\left(\frac 1{\sqrt2}\right)^3 +\frac 12\log \frac{1+\frac 1{\sqrt 2}}{1-\frac 1{\sqrt 2}} \ \right] \\ &= \frac 14 + \frac 1{4\sqrt 2}\log(\sqrt2+1)) \ . \end{aligned} $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.